A first-principles study of the structural, mechanical and electronic properties of precipitates of Al2Cu in Al–Cu alloys. Issue 2 (12th December 2017) - Ouyang, Y. F.; Chen, H. M.; Tao, X. M.; Gao, F.; Peng, Q.; Du, Y.
Abstract : The formation enthalpies of precipitates of Al–Cu are all negative, suggesting that they are all thermodynamically stable. Abstract : The properties of precipitates are important in understanding the strengthening mechanism via precipitation during heat treatment and the aging process in Al–Cu based alloys, where the formation of precipitates is sensitive to temperature and pressure. Here we report a first-principles investigation of the effect of temperature and pressure on the structural stability, elastic constants and formation free energy for precipitates of Al2 Cu, as well as their mechanical properties. Based on the formation enthalpy of Guinier–Preston (GP(I)) zones, the size of the GP(I) zone is predicted to be about 1.4 nm in diameter, which is in good agreement with experimental observations. The formation enthalpies of the precipitates are all negative, suggesting that they are all thermodynamically stable. The present calculations reveal that entropy plays an important role in stabilizing θ-Al2 Cu compared with θC ′-Al2 Cu. The formation free energies of θ′′-Al3 Cu, θC ′-Al2 Cu, θD ′-Al5 Cu3 and θt ′-Al11 Cu7 increase with temperature, while those of θ′-Al2 Cu, θO ′-Al2 Cu and θ-Al2 Cu decrease. The same trend is observed with the effect of pressure. The calculated elastic constants for the considered precipitation phases indicate that they are all mechanically stable and anisotropic, except θC ′-Al2 Cu. θD ′-Al5 Cu3 has the highest Vicker's hardness. The electronic structures are also calculated to gain insight into the bonding characteristics. The present results can help in understanding the formation of precipitates by different treatment processes.